Pengaruh Preferensi Dan Motivasi Wisatawan Gen Z Terhadap Minat Berkunjung Ke Atlas Beach Club - Salurante, Kinaya Louise; Widhyandanta, I Gede Dirga Surya Arya; Sari, Retno Juwita (Institut Pariwisata dan Bisnis Internasional, 2025)
Penelitian ini bertujuan untuk mengetahui preferensi wisatawan dan motivasi wisatawan secara parsial dan simultan terhadap minat berkunjung ke Atlas Beach Club Sampel yang digunakan dalam penelitian ini sebanyak 286 responden. Teknik analisis data yang digunakan dalam penelitian ini adalah Uji Asumsi Klasik, Anaisis Regresi Linier Berganda, Uji Koefisien Determinasi, dan Uji t. Dari hasil penelitian dapat dilihat bahwa Preferensi wisatawan berpengaruh positif signifikan terhadap minat berkunjung, motivasi wisatawan berpengaruh negatif signifikan terhadap minat berkunjung, dan secara simultan Preferensi wisatawan dan motivasi wisatawan berpengaruh signfikan terhadap minat berkunjung. Besarnya Preferensi wisatawan dan motivasi wisatawan terhadap minat berkunjung adalah 55,6%. Saran yang dapat diberikan peneliti adalah pihak Atlas Beach Club diharapkan terus melalukan inovasi, agar nantinya selalu dapat memberikan pengalaman yang sesuai dengan tren dan gaya hidup, selalu meyediakan fasilitas yang berbeda dari pesasasing, untuk memberikan hiburan dan suasana yang berbeda bagi pengunjung, dan menyediakan fasilitas yang lengkap dan berkualitas, serta pelayanan yang baik. Blimbingsari Tourism Village has potential and resources that can be developed and managed with the attachment of community participation. Tourism potential is collaborated with maximum community participation can achieve the dimensions of the implementation of Community Based Tourism so that it can support the realisation of sustainable tourism. The purpose of this research is to 1). Know the natural and cultural tourism potential of Blimbingsari Tourism Village, 2). Knowing the form of community participation involvement, and 3). Knowing the success of CBT in managing tourist villages to realise sustainable tourism. The research method used used a qualitative approach. Data were collected using observation, interview and documentation techniques. The sources of this research are the parties involved in the management of tourist villages, namely Perbekel, BUMDES, Tourism Committee and Village Community. The results of this study indicate that the development of tourist villages has implemented the CBT indicators, namely the economic, environmental, cultural, social and political dimensions. However, in the political dimension there is a lack of success rate indicators because young people have not optimally participated in tourism activities. This study aims to determine tourist preferences and tourist motivations partially and simultaneously towards the interest in visiting the Atlas Beach Club. The sample used in this study was 286 respondents. The data analysis techniques used in this study were the Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test, and t-test. From the results of the study, it can be seen that tourist preferences have a significant positive effect on interest in visiting, tourist motivation has a significant negative effect on interest in visiting, and simultaneously tourist preferences and tourist motivation have a significant effect on interest in visiting. The magnitude of tourist preferences and tourist motivation towards interest in visiting is 55.6%. The suggestion that can be given by the researcher is that the Atlas Beach Club is expected to continue to innovate, so that later it can always provide an experience that is in accordance with trends and lifestyles, always provide different facilities from other tourists, to provide different entertainment and atmosphere for visitors, and provide complete and quality facilities, as well as good service